Ibn Khaldun on the role of knowledge, skills and values in the rise and fall of civilizations : implications for muslim educators in the 21st century. - Ssekamanya, Siraje Abdallah (IIUM Press, International Islamic University Malaysia, 2007)
This paper examines Ibn Khaldun s discussion, in his Muqaddimah,of the role played by knowledge, skills, systems and values in the rise and fall of civilizations to find out how contemporary Muslim societies can benefit from his thought as they grapple with the challenges of globalization and survival in a knowledge-based economy. An attempt is made to link this with his seminal idea of 'asabiyyah (group cohesion) and ethical living in urban dwellings.Ibn Khaldun emphasized, among others, the development of critical and creative thinking skills among Muslim students, the provision of enough job opportunities, justice and the respect of human rights by the rulers, and the proper matching of labor with the skills of workers for better productivity. He asserted that whereas values ultimately lead to the ascension of a society, vices inevitably destroy it. Of particular significance for contemporary Muslims is Ibn Khaldun s contention that science and technology education are crucial in the rise of a Muslim civilization. For these to be useful,however, science and technology must be coupled with a comprehensive religious education. A number of lessons and implications are drawn from the above ideas for contemporary Muslim educators. It is hoped that these could serve as the first steps for the Ummah s return to its rightful position as the center of human civilization.